2021
DOI: 10.3390/vetsci8120320
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Potential of the Oleoresin from the Amazonian Tree Copaifera reticulata with an Unusual Chemical Composition in Rats

Abstract: Copaifera reticulata Ducke is a popularly known species known as copaíba that is widely spread throughout the Amazon region. The tree yields an oleoresin which is extensively used in local traditional medicine mainly as an anti-inflammatory and antinociceptive agent. The aim of the present study was to assess the anti-inflammatory potential of this oleoresin obtained from a national forest in the central Amazon which presented an unusual chemical composition. The chemical composition of volatile compounds of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Consistent with the effects observed in mice, the panaxynol extracted from S. Divaricata roots can markedly ameliorate acute liver injury caused by LPS and D-galactosamine, which implies it has anti-inflammatory activity in vivo 29 . The anti-inflammatory properties of other main components in VOA and VOR, such as spathulenol, neophytadiene, phytone and β-bisabolene, have also been demonstrated in the previous reports 31 – 34 . These reported compounds also partly explained the anti-inflammatory effect of VOA and VOR.…”
Section: Discussionmentioning
confidence: 57%
“…Consistent with the effects observed in mice, the panaxynol extracted from S. Divaricata roots can markedly ameliorate acute liver injury caused by LPS and D-galactosamine, which implies it has anti-inflammatory activity in vivo 29 . The anti-inflammatory properties of other main components in VOA and VOR, such as spathulenol, neophytadiene, phytone and β-bisabolene, have also been demonstrated in the previous reports 31 – 34 . These reported compounds also partly explained the anti-inflammatory effect of VOA and VOR.…”
Section: Discussionmentioning
confidence: 57%
“…The oleoresin of Copaifera reticulata has several compounds that guarantee its various biological activities, and these are mainly attributed to its main compounds [ 2 , 3 , 5 , 12 , 14 , 15 , 37 ]. In this study, when Copaifera reticulata Ducke was characterized by gas chromatography mass spectrometry (GC-MS) [ 10 ], it presented β-caryophyllene as a major component (37.3%), which is a ligand of the cannabinoid receptor 2 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…When binding to this receptor, it blocks the activation of NF-κB, decreasing the synthesis of interleukin 6 (IL-6) [ 37 , 38 ]. This compound also downregulates other proinflammatory cytokines, such as IL-1β, prostaglandin E2, and tumor necrosis factor-alpha, as well as anti-inflammatory cytokines such as IL-6 [ 14 , 37 , 39 , 40 ]. Additionally, some investigations have shown that β-caryophyllene can minimize the expression of nitric oxide (NO), which is a free radical associated with periodontitis, because it is related to an inflammatory process and can induce osteoclast activation [ 13 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural-substance-derived medicines are capable of treating approximately 80% of all the diseases that affect humanity. These medicines exhibit various pharmacological activities such as antimicrobial, anti-inflammatory, antiproliferative, anticoagulant, antiparasitic, and immunosuppressant activities, among others [8][9][10].…”
Section: Introductionmentioning
confidence: 99%